Growth hormone release during sleep in growth-retarded children with normal response to pharmacological tests. Issue 6 (June 1978) - Cacciari, E; Coccagna, G; Cicognani, A; Pirazzoli, P; Gallassi, R; Farneti, P; Bernardi, F; Zappulla, F; Gobbi, G; Verucchi, P
Abstract : Twenty-one prepubertal children of small stature, 10 boys and 11 girls, aged from 4-3 to 12-8 years, were studied. Their height was less than 3rd centile, and during the preceding year all had a growth rate less than 4-5 cm/year. Arginine and L-dopa tests were given, and the release of growth hormone (GH) during monitored sleep was investigated. On the basis of the electroencephalogram and horizontal electro-oculogram, sleep was divided into stages 1-2-3-4 and rapid-eye-movement. All the children had a GH response greater than 8 ng/ml in at least one of the two pharmacological tests, and were therefore accepted as not suffering from GH deficiency. In all 21 children during sleep there was at least one secretory peak with GH greater than 8 ng/ml. Of a total of 46 secretory peaks recorded, 22 (48%) took place during deep, slow sleep (stages 3-4), 10 (22%) during light sleep (stage 2), 10 (22%) during REM sleep, and 4 (8%) during wakening. In 4 patients (19%) no secretory peak was observed during stages 3-4, even though there were peaks at other times. The data (a) show that it is essential to monitor GH throughout the night to ascertain with certainty the presence or absence of physiological secretory peaks of GH; (b) emphasise the rare disagreement between pharmacological and physiological tests; (c) suggest the use of this physiological test for GH secretion in those cases where the insulin test may be hazardous.